(untitled) (Research, Society and Development, 2021)
Objective: To know the perception of professionals about the emergency energy harmonization of an integrative and complementary health practices service. Method: This is a descriptive and qualitative study that used convergent care research as a methodological framework and had as a scenario the Integrative and Complementary Practice Laboratory of the Federal University of Rio Grande do Norte. Data collection occurred between April and June 2021.Semi-structured interviews were conducted, for Google Meet, with an average duration of 30 minutes, to investigate the professionals’ understanding of energy harmonization care. For data organization and analysis, the Collective Subject Discourse method was chosen, the collected statements were methodologically treated using the Software DSCsoft20. Results: 10 professionals participated. The main ideas extracted from the interviews were: Special relationship with integrative practices, relationship of the Serciente, therapists with these practices; Therapist experience with Reiki and Massage practices; Integrative practices for the therapist’s self-development, integrative practices as a strategy to promote the well-being of the Serciente; difficulties and weaknesses of energy harmonization and suggestions for improvements. Conclusion: The discourses present in this work highlighted the importance of Emergency Harmonization for professionals working in this service, awakening reflection about the process, pointing out the opportunities for growth, also highlighting the weaknesses present in the service, as well as pointing out suggestions for improvement so that this activity is best developed.